Kirčio atitraukimo į proklitiką savitumai rytinėje šiaurės žemaičių tarmėje - Murinienė, Lina; Girdenis, Aleksas (Baltistica, 2001)
PECULIARITIES OF THE STRESS SHIFT TO THE PROCLITIC IN THE NORTH–EASTERN ŽEMAITISH DIALECTThe paper is devoted to a detailed analysis of the specific features of the stress shift in the Northeastern part of the North Žemaitish dialect with special attention drawn to the fluctuation of the accent of the proclitic morphs – such as prepositions or negation, e.g. pri ̮ʹkatrũo || ʹprì ̮ katrũo ‘to every one’, i ̮ʹžàbùs ||  ʹi ̮ žàbùs ‘into the brushwood’. Statistical investigation shows that the shift of stress not to the proclitic, but to the first syllable of the stem is typical only for the northernmost edge of the eastern part of the area (especially frequently – in the environs of Vegẽriai) and for the oldest generation of informants – even in the centre of the dialect, Akmẽnė.The observed phenomenon may be interpreted as a result of intimate contacts with the Latvian, very typical of this dialectal area. It is well known that all Latvian dialects have the fixed stress on the first syllable, which (unlike, e.g., the Czech stress) is never shifted to the proclitic.